The crystal structure of 10-(1-bromoethyl)-14-(bromomethyl)dibenzo[a, c]acridine, C24H17NBr2 - Gao Yuan; Liu Tao; Ke Pingping; Jia Fei; Zhang Yuqi; Wang Jijiang; Yue Erlin (Zeitschrift für Kristallographie - New Crystal Structures)
C24H17NBr2, monoclinic, P21/n (no. 14), a = 9.6466(19) Å, b = 14.030(3) Å, c = 13.894(3) Å, β = 100.95(3)°, V = 1846.2(7) Å3, Z = 4, Rgt(F) = 0.0440, wRref(F2) = 0.0970, T = 173(2) K.